Legal Education on Inheritance Law for Family Conflict Mitigation - SAG, Syahid Hidayatulloh; Budiwati, Anisah (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2025)
This research discusses the role of inheritance law education in preventing family conflicts in Indonesia. Ignorance and lack of understanding regarding inheritance law often trigger family conflicts, particularly in matters of inheritance, and can potentially lead to acts of violence. This research aims to explain how education on inheritance law can enhance public understanding of the rights and obligations of heirs and prevent conflicts. The research was conducted using a normative legal method based on literature studies, employing a statutory law approach to analyze relevant regulations. From this research, it can be concluded that in Indonesia, the inheritance legal system is pluralistic and refers to three different legal systems: customary inheritance law, civil inheritance law (Burgerlijk Wetboek), and Islamic inheritance law. Inheritance law in Indonesia has significant urgency because ignorance of inheritance law can cause family conflicts that damage relationships between family members and even potentially lead to greater problems such as physical abuse and even murder. Therefore, the role of inheritance law education is very important in Indonesia, which can be conducted through counseling, mass media, legal aid institutions, and community service programs. Through various efforts that can be made related to inheritance law education, public awareness regarding inheritance law can be sparked, thereby minimizing conflicts within families related to inheritance or conflicts based on inheritance matters.